DETERMINATION OF EQUIVALENT CIRCUIT PARAMETERS FOR THREE-PHASE INDUCTION MOTORS: PROCEDURE IN ACCORDANCE WITH THE IEC 60034-28 STANDARD - Mlakar, Matej; Hadžiselimović, Miralem; Štumberger , Bojan; Zagradišnik, Ivan (Journal of Energy Technology, 2024)
Currently, an increasing number of induction motors are being used in liaison with converters, and it is necessary to know the equivalent circuit parameters of the induction motor. In this article, we have calculated equivalent circuit parameters based on the measurement as presented in IEC 60034-28. To evaluate the parameters’ results calculated based on the IEC 60034-28 standard, a comparison is made with a calculation from the emLook analytical software package.